From blitzkrieg to blitzscaling: Assessing the impact of venture capital dynamics on military norms - Elke Schwarz (Finance and Society)
Venture capital (VC) has recently emerged as a powerful new actor in the military domain. In the USA, VC investment in defence startups doubled between 2019 and 2022. A similar trend is noticeable in Europe, where billions are funnelled into AI-drone startup companies, spurred by escalating conflicts around the globe. VC investment is a ‘high-risk-high-reward’ way of financing military technologies, which requires fast-paced exponential growth at scale (‘blitzscaling’) and the disruption of existing markets. But with disruption comes debris. What happens when military organisations, which must navigate ethical questions pertaining to life and death, become shaped in the image of Silicon Valley and VC funding? This paper argues that the VC sector exerts a significant influence not only on military procurement processes but also on the direction of military operations and practices. This, in turn, has potentially significant effects on the communities and stakeholders affected by military operations, including those caught in the crosshairs of VC-backed AI technologies.